Shakespeare in Digital Games and Virtual Worlds - Timplalexi, Eleni (Multicultural Shakespeare: Translation, Appropriation and Performance, 2018)
Shakespeare’s plays have long flirted with using various artistic and medial forms other than theatre, such as cinema, music, visual arts, television, comics, animation and, lately, digital games and virtual worlds. Especially in the 20th and 21st century, a fascination with Shakespeare both as a historical and theatrical figure and as a playwright has become evident in screen based media (cinema, television and video), ranging from “faithful,” almost documented performances of his plays to free style adaptations or vague film references. Digital games and virtual worlds carry on this tradition of the transmedial journey of Shakespeare’s plays to screen based media but top it up with new forms of interaction and performativity. For the first time in the history of mankind everyone can enjoy firsthand from his armchair and for free the experience of taking part in a play by the Bard by entering a virtual world as if it was a stage and by assuming roles through avatars. The article attempts first to introduce the reader to the deeper needs that gave rise to animation, a fundamental aspect of digital gaming and virtual worlds. It then tries to illuminate the various facets of digital performance and gaming, especially in relation to Shakespeare-themed and inspired digital games and virtual worlds, by putting forward some axes of classification. Finally, it both suggests some ideas that may be of use in rendering the Shakespeare gaming experience more “complete” and “theatrical” and ends by acknowledging the immense potential for the exploration of theatricality and performativity in digital games and virtual worlds.